PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA DINAS KEBAKARAN DAN PENANGGULANGAN BENCANA KOTA BANDUNG - Shanti Ramdhani; Dian Indiyati (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The purpose of this study is to find out how much influence the work environment and work motivation have on employee performance both partially and simultaneously in the Bandung City Fire and Disaster Management Service. The type of research used in this research is quantitative research. Data collection methods taken in this study were interviews and questionnaires. The sample in this study is a saturated sample, because all members in the population can be used as a sample, amounting to 141 employees of the Bandung City Fire and Disaster Management Service. The analysis used in processing the data in this study is Structural Equation Modeling (SEM) with SmartPLS software version 3.2.9. The results obtained in this study stated that there was a positive and significant influence between work environment variables and work motivation on employee performance at the Bandung City Fire and Disaster Management Service both partially and simultaneously.